2015
DOI: 10.1080/09712119.2015.1091337
|View full text |Cite
|
Sign up to set email alerts
|

Influence of catechin (flavan-3-ol) addition to breeder quail (Coturnix coturnix japonica) diets on productivity, reproductive performance, egg quality and yolk oxidative stability

Abstract: The aim of this study was to investigate the effect of green tea (Camellia sinensis) catechin addition to breeder quail (Coturnix coturnix japonica) diet on productivity, reproductive performance, egg quality and yolk malondialdehyde (MDA) levels during storage, and some serum biochemical parameters. In this study, a total number of 180 quail, 7 weeks of age were randomly divided into 3 groups (1 control group and 2 treatment groups) with 5 replicates (9 females + 3 males). The control group was fed basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…(2016) noticed that the inclusion of green tea extract in poultry diet at different concentrations (0.125, 0.25, 0.5, 1.0 and 2.0 g/kg) does not improve growth performance. Also, there was no positive effect found of feeding diet included with 0.2% and 0.4% catechin extracted from green tea for 35 days on growth performance and egg production of breeder quail (Kara et al., 2016).…”
Section: Effect Of Polyphenols On Poultry Performancementioning
confidence: 99%
“…(2016) noticed that the inclusion of green tea extract in poultry diet at different concentrations (0.125, 0.25, 0.5, 1.0 and 2.0 g/kg) does not improve growth performance. Also, there was no positive effect found of feeding diet included with 0.2% and 0.4% catechin extracted from green tea for 35 days on growth performance and egg production of breeder quail (Kara et al., 2016).…”
Section: Effect Of Polyphenols On Poultry Performancementioning
confidence: 99%
“…Flavonoids are found in fruit, vegetables, grains, bark, roots, stems, flowers, tea, and wine, all have variable phenolic structures (Panche et al 2016). These structures have many pharmacological effects, such as antioxidant, antimicrobial, anticarcinogenic, hypo-allergic, hypoglycaemic and anti-inflammatory activity (Biswas et al 2000;Kara and Güçlü 2012;Kara et al 2016a;2016b;2016c;2016d). Many of these effects are related to their antioxidant properties and are important in both human and animal nutrition (Mahmoud et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that green tea or its polyphenols has been used as an ingredient or feed additive in animals such as laying hen, broiler and dog (Biswas and Wakita 2001;Uuganbayar et al 2005;Kim and Yang 2010;Kara et al 2016b). In previous studies, it was stated that catechin supplementation to poultry diet decreased the lipid peroxidation of the liver, blood and egg and increased the reproductive performance (fertility, hatchability and hatchability of fertile eggs), meat quality and the self-life of animal products (Kara et al 2016b(Kara et al , 2016c. Besides, dietary catechin highly increased the excretion of Zn, Mg and Cu via the faces, but increased Se level in serum (Kara et al 2016d) and it negatively affected external quality parameters of egg (Kara et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Green tea can prevent dental caries and reduce cholesterol and lipid absorption in the gastrointestinal tract ( Koo and Cho, 2004 ). Catechins, the major component in tea polyphenols, can decrease the plasma and liver MDA concentrations, as well as serum glucose and total cholesterol levels and have the potential to increase meat quality in fattening quail ( Kara et al., 2016a ). Xia et al.…”
Section: Introductionmentioning
confidence: 99%